Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Bagi Hasil terhadap Belanja Modal - Sifa Asri Trisnani; Wikan Isthika (Jurnal Akuntansi Indonesia, 2022)
This study aims to examine the effect of regional taxes, regional retribution, general allocation funds, special allocation funds and revenue sharing funds on capital expenditure in regencies/cities in Central Java. The study is based on agency theory. The population in this study were 35 regencies/cities in Central Java. The analytical method used is multiple linear regression with the help of the SPSS program. The study found amongst the independent variables the regional tax, regional retribution, general allocation fund, special allocation funds, revenue sharing funds had significant effect on the capital expenditure regencies/cities in Central Java. The coefficient of determination (R2) of 0.732 indicates that the five independent variables contributed to 73.2% of the variance in the dependent variable.